Preventing the Incidence of Severe Preeclampsia by Maintaining an Ideal Body Weight During Pregnancy - Ferawati, Emi; Pritalianto, Hushat; Sepalanita, Widya (Faculty of Medicine, Universitas Padjadjaran, 2025)
Preeclampsia is a pregnancy-specific disease potentially leading to complications, morbidity, and mortality. In general, obesity may cause preeclampsia through several common mechanisms. This study aimed to examine the association between obesity and the incidence of severe preeclampsia (SP) at Dr. Dradjat Prawiranegara General Hospital, Serang, Indonesia. A retrospective cohort design was used and the sample comprised of 168 parturients (84 SP and 84 non-SP subjects). Sample selection was consecutively conducted from June to November 2023, while data were analyzed using the Chi-Square test and multivariable analysis with multiple logistic regression. There was a statistically significant relationship between nutritional status and obesity in participants with SP history (p<0.05). Obese women had a 2.96 times higher risk of developing SP compared to non-obese. Additionally, the study found that multigravidas (≥G2) had a 2.19 times higher risk of suffering from SP compared to primigravidas (G1) (p=0.019). Furthermore, women who only completed ≤ junior high school education had a 2.14 times higher risk of suffering from SP compared to those who completed ≥ high school (p=0.060). In conclusion, women in delivery who suffered from obesity have a 2.68 times greater risk of suffering SP than non-obese, as evident from both bivariable and multivariable analyses.